Security of cloud computing technology - Khummanee, Suchart (Asia-Pacific Journal of Science and Technology, 2017)
This article is explained problems and solutions to solve security problems of cloud computing technology which is the high-performance computer system. It is a very interesting topic at present. The aims of this technology are for respond processing of large amounts of data, complexity, flexibilities for applications and reduce the cost of processing. Currently this technology is still at its beginning stage of practical use. Thus, the security problems are still important and interesting problem at present.